2018
DOI: 10.1038/s41598-018-30378-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Use of Influenza Forecasts and Epidemiological Modeling in Public Health Decision Making in the United States

Abstract: Although forecasts and other mathematical models have the potential to play an important role in mitigating the impact of infectious disease outbreaks, the extent to which these tools are used in public health decision making in the United States is unclear. Throughout 2015, we invited public health practitioners belonging to three national public health organizations to complete a cross-sectional survey containing questions on model awareness, model use, and communication with modelers. Of 39 respondents, 46.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Our findings are strikingly similar to those of Doms et al, 9 within a different area of work (HHWS/HHAPs versus influenza forecasts) and using different methods (qualitative versus quantitative). More broadly, such observation suggests this issue might be observed in other areas in public health and pinpoints the importance of researchers in public health to work in close contact with practitioners, using less statistical or methodological terms.…”
Section: What This Study Addssupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are strikingly similar to those of Doms et al, 9 within a different area of work (HHWS/HHAPs versus influenza forecasts) and using different methods (qualitative versus quantitative). More broadly, such observation suggests this issue might be observed in other areas in public health and pinpoints the importance of researchers in public health to work in close contact with practitioners, using less statistical or methodological terms.…”
Section: What This Study Addssupporting
confidence: 90%
“…7,8 However, good communication is also required between professionals working in public health, and the issue of communication within public health has received less attention. Doms et al 9 employed an online survey to assess awareness and use of influenza forecasts in decision making among US public health professionals. These authors reported that less than half of the respondents reported to use such models; over half referred the need for improved communication between practitioners and modellers and the use of less technical language while discussing models.…”
Section: What Is Already Known On the Topicmentioning
confidence: 99%
“…However, the use of infectious disease forecasts for decision making is challenging because most existing infectious diseases forecasts are not standardized, not validated, and can be difficult to communicate to non-scientific audiences. Forecasts may fail to address outcomes that are relevant for public health responders [10]. To address these limitations, the Centers for Disease Control and Prevention’s (CDC) Influenza Division (CDC/ID) and Division of Vector-Borne Diseases launched the Epidemic Prediction Initiative (EPI) in December 2014 [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, epidemic forecasting algorithms that leverage routine surveillance data can also be used to rapidly predict pandemic characteristics relevant to policy makers. Every year during the influenza season, modelers in many parts of the world, sometimes in collaboration with public health practitioners, make weekly forecasts of epidemic characteristics, such as peak size and timing [35][36][37]. Since 2013, the United States Centers for Disease Control and Prevention (CDC) have even coordinated seasonal challenges to external researchers to predict onset week and peak week for the US influenza season [38].…”
Section: The Importance Of Situational Awarenessmentioning
confidence: 99%